2013
DOI: 10.1061/(asce)co.1943-7862.0000588
|View full text |Cite
|
Sign up to set email alerts
|

Determining Safety Climate Factors in the Repair, Maintenance, Minor Alteration, and Addition Sector of Hong Kong

Abstract: Accident record of the repair, maintenance, minor alteration, and addition (RMAA) sector has been alarmingly high; however, research in the RMAA sector remains limited. Unsafe behavior is considered one of the key causes of accidents. Thus, the organizational factors that influence individual safety behavior at work continue to be the focus of many studies. The safety climate, which reflects the true priority of safety in an organization, has drawn much attention.Safety climate measurement helps to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 38 publications
1
72
0
Order By: Relevance
“…The correlation between factors 1 and 2 is significant (ρ< 0.05) at 0.448, but not large enough (≥0.85) to cause multicollinearity or discriminant validity problems (Kenny, 2016). The results of the discriminant validity test showed that the structure has dissimilar constructs for the two factors because the AVE of factor 1 (INT = 0.649) and factor 2 (EXT = 0.736), are greater than the squared factor correlation between INT and EXT (R 2 = 0.230) (Hon, et al, 2012). Finally, the internal consistency of observed variables within latent variables, (known as construct reliability), and calculated based on Equation 1, for INT and EXT are 0.808 and 0.821 respectively, was above the "good quality" level of 0.70 (Bagozzi & Yi, 1988).…”
Section: Confirmatory Factor Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…The correlation between factors 1 and 2 is significant (ρ< 0.05) at 0.448, but not large enough (≥0.85) to cause multicollinearity or discriminant validity problems (Kenny, 2016). The results of the discriminant validity test showed that the structure has dissimilar constructs for the two factors because the AVE of factor 1 (INT = 0.649) and factor 2 (EXT = 0.736), are greater than the squared factor correlation between INT and EXT (R 2 = 0.230) (Hon, et al, 2012). Finally, the internal consistency of observed variables within latent variables, (known as construct reliability), and calculated based on Equation 1, for INT and EXT are 0.808 and 0.821 respectively, was above the "good quality" level of 0.70 (Bagozzi & Yi, 1988).…”
Section: Confirmatory Factor Analysismentioning
confidence: 99%
“…5 and ≤1.0) for standardized factor loading in construction management research (e.g. (Hon, et al, 2012;Oladinrin & Ho, 2015;Xiong, et al, 2015b). Of note is the reduced number of the observed variables (or indicators) of owner commitment from eight (OC1-OC8) to three (OC2-OC4).…”
Section: Confirmatory Factor Analysismentioning
confidence: 99%
See 3 more Smart Citations